2007
DOI: 10.1021/jp0762370
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies on the Mechanism of C−P Bond Cleavage of a Model α-Aminophosphonate in Acidic Condition

Abstract: Various reaction paths of the P-C bond cleavage of alpha-aminophosphonates in acidic media, resulting in the derivatives of phosphonic acid, has been investigated using density functional level of theories in the gas phase as well as in aqueous medium. Dimethyl (alpha-anilinobenzyl)phosphonate has been used as the model molecule and our investigation confirms a three steps process including protonation, P-C bond cleavage, and the transformation of the products from the final transition state (imine cation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…Both forms facilitate the elimination to P III (increased concentration of non-protonated Nphenyl amine nitrogen) and lower the reaction rate of decomposition to P V (decreased concentration of the protonated pyridine nitrogen which is necessary to form a good leaving group). 28,47 This observation has been reported independently by Boduszek et al 26,45 and by Kiersnowska. 27 In this case the phosphorus III and phosphorus V derivatives are easily distinguished, the former appears in its 31 …”
Section: Thermodynamic Studiesmentioning
confidence: 52%
See 4 more Smart Citations
“…Both forms facilitate the elimination to P III (increased concentration of non-protonated Nphenyl amine nitrogen) and lower the reaction rate of decomposition to P V (decreased concentration of the protonated pyridine nitrogen which is necessary to form a good leaving group). 28,47 This observation has been reported independently by Boduszek et al 26,45 and by Kiersnowska. 27 In this case the phosphorus III and phosphorus V derivatives are easily distinguished, the former appears in its 31 …”
Section: Thermodynamic Studiesmentioning
confidence: 52%
“…This study confirmed that a three-step process including amino-group protonation, proton transfer through a hydrogen-oxygen bond NH•••O(P), 43 and P-C bond cleavage, leading to a protonated imine and derivatives of H-phosphonate is the most probable mechanism. 6,27,28,43,44 It should be noted that for N-alkyl aminophosphonates the decomposition is not observed as the amine nitrogen in this case is protonated and formation of imine (leaving group) is prevented. Lowering the basicity of the amine as is the case in the N-benzhydryl derivative, again facilitates the elimination process 47 Decomposition to P V .…”
Section: Thermodynamic Studiesmentioning
confidence: 94%
See 3 more Smart Citations